Stan kadr administracji publicznej z perspektywy ogólnokrajowej i regionalnej - Korczak, Jerzy (Studia Prawa Publicznego, 2019)
This paper tackles staff problems of contemporary public administration. It starts with an analysis of the dependence between the efficiency of administration and the effi ciency of public servants in administration, whose efficiency depends on the level and quality of their qualifications. The analysis was carried out in three perspectives (i) with regard to the whole public administration of the State, (ii) with regard to the State and government central administration and (iii) with regard to regional public administration, on the example of the Lower Silesia region. It was assumed that the quality of the staff in administration is related to and depends on the legislation regulating the recruitment for public administration offices. The relevant provisions determine the choices made in the recruitment process and the subsequent creation of career paths. However, unstable and poor legal provisions have a negative impact on the quality of public administration personnel, which is manifested in poor performance, high employment fl uctuations and a diminishing interest among the younger generation in a career in public administration. This, in turn, may distort the natural generation exchange of administration staff in the future. As can be seen from the statistical analysis conducted in respect of the numbers of public administration employees and the fluctuation among them, as well as the demographic structure examined with regard the gender, age and length of employment, the initially assumed hypothesis of the negative consequences of the inconsistent legislative policy governing the regulations of the public administration staff. The sociological picture illustrating the attitudes among the members of the society to public administration confirms the hypothesis of the poor condition of public administration and a loss in confi dence in its activities or actions. The main reason for the current situation is that the constitutional principle of the neutrality of civil servants is realised only by orders that prohibit combining civil service with political activity, but do not limit or reduce the strong and direct influence exercised by political parties on the legal regulations within public civil service or the policies of appointing candidates to key administrative positions in (not only government) offices.